Let's Talk About Fixed Effects: Let's Talk About All the Good Things and the Bad Things - Matthias Collischon; Andreas Eberl (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2020)
With the broader availability of panel data, fixed effects (FE) regression models are becoming increasingly important in sociology. However, in some studies the potential pitfalls of these models may be ignored, and common critiques of FE models may not always be applicable in comparison to other methods. This article provides an overview of linear FE models and their pitfalls for applied researchers. Throughout the article, we contrast FE and classical pooled ordinary least squares (OLS) models. We argue that in most cases FE models are at least as good as pooled OLS models. Therefore, we encourage scholars to use FE models if possible. Nevertheless, the limitations of FE models should be known and considered.
Keywords: 300; Fixed effects; Quantitative methods; Causality; Panel data; Exogeneity; Fixed effects; Quantitative Methoden; Kausalität; Paneldaten; Exogenität